Training of university teachers in interdisciplinary postgraduate courses. Difficulties in writing the Thesis Plan - Pozzo, María Isabel (2021)
Introduction: Postgraduate studies allow university graduates to continue their professional development, even in disciplines different from their previous studies. To this end, postgraduate courses require students to prepare a thesis plan as a prior step to completing a thesis, a central requirement of this educational level. These requirements involve knowledge that is not always provided in the various graduate courses. Objective: In this context, in this paper we present an analysis of the main writing difficulties identified in Thesis Plans written by university teachers from different areas of knowledge within the framework of a master’s degree in university teaching training in Argentina. Method: For this, 13 thesis plans presented to pass the final Master’s Seminar are compiled and adopted as units of analysis. An exhaustive correction of each Plan is made; then, the difficulties encountered are categorized into microstructural, macrostructural and superstructural (Van Dijk, 1980) and in turn subcategorized. Results: The results show a significant amount and variety of difficulties in the three categories in all the students. Conclusion: From the amount and variety of difficulties found, the need to design and implement comprehensive teaching practices to complete the thesis is concluded.